Spoken Pangasinan - Benton, Richard A. (University of Hawai'i Press, 2018)
The Philippine series of the PALI Language Texts, under the general editorship of Howard P. McKaughan, consists of lesson textbooks, grammars, and dictionaries for seven major Philippine languages.